2015
DOI: 10.1242/bio.20148615
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid droplet dynamics in Saccharomyces cerevisiae depends on the Rab7-like Ypt7p, HOPS complex and V1-ATPase

Abstract: It has now been clearly shown that lipid droplets (LDs) play a dynamic role in the cell. This was reinforced by LD proteomics which suggest that a significant number of trafficking proteins are associated with this organelle. Using microscopy, we showed that LDs partly co-localize with the vacuole in S. cerevisiae. Immunoblot experiments confirmed the association of the vacuolar Rab GTPase Rab7-like Ypt7p with LDs. We observed an increase in fatty acid content and LD number in ypt7Δ mutant and also changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 87 publications
3
30
1
Order By: Relevance
“…Microscopic and proteomic analysis demonstrated that Ypt7p is associated with LDs in yeast grown in poor medium. Defective Ypt7p strains have increased FFA content and numbers of LDs in low nutrient conditions [26]. Together with the previous mammalian findings, these studies indicate that Rab7 may be a conserved regulator of lipophagy.…”
Section: Targeting Lds For Selective Autophagysupporting
confidence: 58%
See 2 more Smart Citations
“…Microscopic and proteomic analysis demonstrated that Ypt7p is associated with LDs in yeast grown in poor medium. Defective Ypt7p strains have increased FFA content and numbers of LDs in low nutrient conditions [26]. Together with the previous mammalian findings, these studies indicate that Rab7 may be a conserved regulator of lipophagy.…”
Section: Targeting Lds For Selective Autophagysupporting
confidence: 58%
“…Consistent with a conserved regulatory role of Rab7 in lipophagy is that the yeast Rab7-like protein Ypt7p regulates LD dynamics and membrane trafficking in S. Cerevisiae [26]. Microscopic and proteomic analysis demonstrated that Ypt7p is associated with LDs in yeast grown in poor medium.…”
Section: Targeting Lds For Selective Autophagymentioning
confidence: 81%
See 1 more Smart Citation
“…These regions have been reported as lipid droplets (LDs) (Bouchez et al, 2015;Wolinski et al, 2011).…”
Section: The C-terminal Of Erg9p Is a Signal Peptide Targeting The Enmentioning
confidence: 99%
“…Endosomes have also been observed to enwrap LDs, potentially promoting the delivery of LDs to lysosomes allowing for the transfer of cholesterol (Martin and Parton, 2005;Ouimet et al, 2011). Even though the interaction of LDs and other organelles (e.g., endosomes, ER, and vacuole) appears to be regulated by several Rab GTPases (Liu et al, 2007;Murphy et al, 2009;Bouchez et al, 2015), and the fusion events between LDs themselves, or LDs and mitochondria likely involves SNARE-mediated homotypic fusion Jägerström et al, 2009;Olofsson et al, 2009), the underlying molecular mechanisms remain largely unknown. In this respect, the LD-associated protein perilipin 5 is regarded as a candidate for the physical and metabolic linkage of mitochondria to LDs (Wang et al, 2011), whereas the molecular basis for a peroxisome-LD interaction remains elusive.…”
Section: Lipid Dropletsmentioning
confidence: 99%